Household Fish Consumption in Peri-urban Areas of Cochin - Gopal, Nikita; V., Radhakrishnan Nair (Fishery Technology, 2025)
Household consumption expenditures of fish in peri-urban areas of Cochin are examined in this paper. Food consumption expenditure as a percentage of household income fell as income increased but the total expenditure per capita on food increased with increasing income. At micro-level, average fish consumption expenditure increased with rising income but percentage consumption expenditure on fish did not show much variation between different income classes. Households in these areas were observed to spend a greater share of the food consumption expenditure on other animal products like meat and milk as income levels increased. Limited choice varieties through a few marketing channels reflecting the general neglect of interior markets and consumers were the main reason for this trend.